The records management program of the Department of Agrarian Reform - Villania, Vaneth Leigh V. (School of Library and Information Studies, University of the Philippines Diliman, 2010)
This study evaluated the records management program of the Department of Agrarian Reform using the National Archives' Guidelines in Records Management or the NAP General Circular No. 1 and NAP General Circular No. 2. Based on Saffady's (2004) Records Management Components, the following were evaluated 1. Records retention; 2.Compliance with Laws and Regulations; 3. Cost-Effective Management of Inactive Records; 4. Organization and Retrieval of Active Records; 5. Protection of Vital Records.